2017
DOI: 10.1371/journal.pone.0172491
|View full text |Cite
|
Sign up to set email alerts
|

Activation of odorant receptor in colorectal cancer cells leads to inhibition of cell proliferation and apoptosis

Abstract: The analysis and functional characterization of ectopically expressed human olfactory receptors (ORs) is becoming increasingly important, as many ORs have been identified in several healthy and cancerous tissues. OR activation has been demonstrated to have influence on cancer cell growth and progression. Here, ORs were identified using RNA-Seq analyses and RT-PCR. We demonstrated the OR protein localization in HCT116 cells using immunocytochemistry (IHC). In order to analyze the physiological role of OR51B4, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 45 publications
2
77
0
Order By: Relevance
“…Forty‐two genes belonged to olfactory receptors (ORs), a supergene family encoding G‐protein coupled proteins. Recent studies showed that some ORs are also expressed in tissues other than olfactory sensory neurons and have been recently suggested as putative drivers of cancers . Unfortunately, we were not able to proceed with the validation of such genes since they were not included among those profiled in dataset we selected as validation cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Forty‐two genes belonged to olfactory receptors (ORs), a supergene family encoding G‐protein coupled proteins. Recent studies showed that some ORs are also expressed in tissues other than olfactory sensory neurons and have been recently suggested as putative drivers of cancers . Unfortunately, we were not able to proceed with the validation of such genes since they were not included among those profiled in dataset we selected as validation cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Olfactory transduction was one of the top-ranked pathways enriched by our predicted hypomethylated Alu in all four tumor tissues of interest. This pathway contains a large gene family of olfactory receptors (ORs), which have been found to be ectopically expressed in non-olfactory tissues ( 93 ) and for some ORs overexpressed in breast ( 94 ), colon ( 95 ), lung ( 96 ) and prostate tissues ( 97 ). In addition, we observed axon guidance pathway was significantly enriched with hypomethylated LINE-1 in breast, colon, and lung cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis and functional characterization of ectopically expressed human ORs is becoming increasingly important as many ORs have been identified in several healthy and cancerous tissues, and show tumor-specific regulation (reviewed in Kang & Koo 2012, see also Weng et al 2005, Cunha et al 2006, Leja et al2009, Cui et al 2013, Giandomenico et al 2013, Pronin et al 2014, Sanz et al 2014, Cao et al 2015, Maßberg et al 2015, Flegel et al 2016, Manteniotis et al 2016ab, Jovancevic et al 2017b, Weber et al 2017). Some ORs have even emerged as specific diagnostic and therapeutic targets for various cancers (Xu et al 2000, Weng et al 2005, Leja et al 2009, Giandomenico et al 2013, Muranen et al 2011, Cui et al 2013, Morita et al 2016) and in the process of wound healing (Busse et al 2014).…”
Section: Lror-variants Show Superior Performance Over the Respective mentioning
confidence: 99%
“…But it is not all they do. Despite their name, many human OR genes are expressed in non-olfactory tissues (Feldmesser et al 2006, Flegel et al 2013, Zhang et al 2004 and have been implicated in: cytokinesis, cell proliferation and migration (Neuhaus et al 2009, Zhang et al2012, Busse et al2014, Sanz et al 2014, Gelis et al 2016, Manteniotis et al 2016ab, Jovancevic et al 2017a, Tsai et al 2017, Weber et al 2017, sperm and monocyte chemotaxis (Spehr et al 2003, Veitinger et al 2011, Li et al 2013b, melanocyte function (Gelis et al 2016(Gelis et al , 2017, serotonin release (Braun et al 2007, Kidd et al 2008, Gu et al 2014, Kalbe et al 2016, insulin secretion (Munakata et al 2018), myocardial function (Kim et al 2015, Jovancevic et al 2017c, and regulation of breathing (Chang et al 2015).…”
Section: Introductionmentioning
confidence: 99%